Predictors of Neonatal Jaundice Admissions: A Comparative Study Between Thai and Myanmar Mothers Residing in Thailand - Eksamut W; Rungamornrat S; Payakkaraung S (Journal of Multidisciplinary Healthcare)
Wimala Eksamut,1 Somsiri Rungamornrat,2 Sudaporn Payakkaraung2 1Master of Nursing Sciences (Pediatric Nursing) (Candidate), Faculty of Nursing, Mahidol University, Bangkok, Thailand; 2Department of Pediatric Nursing, Faculty of Nursing, Mahidol University, Bangkok, ThailandCorrespondence: Somsiri Rungamornrat, Faculty of Nursing, Mahidol University, Bangkok, Thailand, Tel +6624197466, Email somsiri.run@mahidol.ac.thPurpose: This study aimed to explore the relationship between maternal health literacy, preventive practices, and neonatal jaundice admissions among Thai and Myanmar mothers.Patients and Methods: A cross-sectional predictive design was employed with 400 mothers of full-term infants, including 200 Thai and 200 Myanmar mothers, recruited from a provincial hospital in Thailand. Data were collected in two phases: baseline demographic and clinical data were obtained before discharge, and maternal health literacy and preventive practices were assessed post-discharge when infants were 4– 5 days old. Logistic regression was used to examine associations between maternal health literacy, preventive practices, and neonatal jaundice admissions, adjusting for covariates such as maternal age and education.Results: Maternal health literacy and preventive practices were significantly associated with reduced neonatal jaundice admissions among Thai mothers. However, after adjusting for covariates, these factors were not independent predictors, suggesting that Thailand’s universal healthcare and postpartum education programs mitigate individual limitations. For Myanmar mothers, maternal health literacy was the sole significant predictor of neonatal jaundice admissions, reflecting its critical role in resource-limited settings. Preventive practices were not significant predictors, likely due to systemic barriers such as language challenges, limited healthcare access, reliance on traditional remedies, and insufficient skills to observe and manage early signs of neonatal jaundice effectively.Conclusion: Maternal health literacy plays a pivotal role in shaping neonatal jaundice outcomes, particularly for immigrant mothers in resource-limited contexts. Strengthening bilingual education, culturally tailored healthcare support, and expanding resources for migrant populations are essential to reducing disparities and improving neonatal outcomes in low- and middle-income countries.Keywords: maternal health literacy, neonatal jaundice, preventive practices, immigrant mothers, low- and middle-income countries (LMICs)